Analisis Sistem Pelayanan dan Pendistribusian Barang dengan Metode Antrian dan Networking Minimum Spanning Tree pada Toko Kelontong Femwyz - Rahman Saleh; Rianita Puspa Sari; Yoane Rahmanita Mulyani; Muhammad Bima Agung (Peneliti.net, 2022)
Micro, Small and Medium Enterprises (MSMEs) are business sectors that have a very significant role in the Indonesian economy. Femwyz Grocery Store is one of the MSMEs that must be developed. Therefore, it is necessary to analyze the operational process. The focus of this research is the analysis of the queuing system and the distribution of goods. The queuing model is used to determine how effective the service system at the Femwyz Grocery Store is. The research also uses the Networking method, namely the Minimum Spanning Tree or the network graph model with the smallest number of weights. This study aims to find the optimal solution in the case under study. The results of the Queue Method in this study are the average waiting time for customers in the system at the Femwyz Grocery Store is 1 hour or 60 minutes. While the results using the Networking (Spanning Tree) method are Grocery Store Femwyz – Jatiragas, Grocery Store Femwyz – Jatisari, Grocery Store Femwyz – Cirejag, Jatisari – Mekarsari, Jatiragas – Cicinde, Cirejag – Cibanggala, Mekarsari – Pacing, Cicinde – Gempol, Gempol – Suka haji with a total distance of 30.9 Km or 30900 Meters